Development of Digital Transformation Maturity Measurements: a Systematic Literature Review - Baihaqy, Ahmad; Subriadi, Apol Pribadi (Journal of Nonformal Education, 2023)
Digital transformation is a phenomenon that provides the right demand and attitude for organizations in digital optimization. Digital transformation encourages organizations to adapt to technological developments as a strategic step to support organizational sustainability and win market competition. The purpose of this article is presenting a systematic literature review of the development of measuring the maturity of digital transformation. The methodology used in this article is systematic literature review approach with article collection strategy that discuss digital transformation and digital maturity measurement and is sourced from reputable journals indexed by Scopus and or the Web of Science. There are 1385 articles appear when searching for digital transformation, out of 1385 there are 30 articles relevant to the topic of digital transformation and digital maturity measurement with the range of 2018-2022. The findings of this systematic literature review have 6 levels and 4 dimensions in measuring the maturity of digital transformation in the industrial sector (large, medium, small), there are 8 levels and 7 dimensions in measuring the maturity of digital transformation in health sector, there are 6 levels and 6 dimensions in measuring the maturity of digital transformation in the banking sector, and there are 5 levels and 5 dimensions in measuring the maturity of digital transformation in the education sector. This article supplies valuable insights on the topic of measuring the maturity of digital transformation and can be an opportunity for further research such as evaluating, developing empirically testing in different sectors of the economy in different regions.